Book Reviews (Journal of Finance, 1982)
ABSTRACT Book reviewed in this article: Issues in Public‐Utility Pricing and Regulation . Edited by MICHAEL A. CREW. Lexington, Mass.: D.C. Heath and Company, 1980. Pp. x + 225. The Economic Effects on Lessees of FASB Statement No. 13, Accounting for Leases . By A. RASHAD ABDEL‐KHALIK et al . Stamford, Conn.: Financial Accounting Standards Board, 1981. Fundamentals of Managerial Finance . By RAYMOND P. NEVEU. Cincinnati: South‐Western Publishing Co., 1981. Pp. viii + 552. The Property Tax Revolt: The Case of Proposition 13 . Edited by GEORGE G. KAUFMAN and KENNETH T. ROSEN. Cambridge: Ballinger Publishing Company, 1981. Pp. 232 + xviii. Finance: A Conceptual Approach . By NAHUM BIGER. Toronto: Butterworths, 1981. Monetary Theory . By Laurence Harris. New York: McGraw‐Hill Book Company, Economics Handbook Series , 1981. Pp. xiii + 481.